The Importance of Replacement Reserve Supervision in Maintaining Hotel Business Reputation: Pentingnya Pengawasan Replacement Reserve Dalam Menjaga Reputasi Bisnis Hotel - I Putu Arnawa; Tuwi, I Wayan; Pua, I Manuel (Jurnal Ilmiah Hospitality Management, 2024)
The hotel industry is one of the most important sectors in the global economy as well as in Indonesia's economy. In its operations, hotels require regular maintenance and upkeep to continue functioning effectively. One crucial aspect of hotel maintenance is the replacement reserve. A replacement reserve refers to funds allocated for the replacement and repair of outdated or damaged hotel equipment and facilities. This paper aims to explore the importance of utilizing replacement reserves in the hotel industry. The data collection method used in this study is literature review from various reliable sources, such as academic books, journals, and hospitality industry reports. The findings of the research indicate that the effective use of replacement reserves can offer significant benefits to the hotel industry. In conclusion, replacement reserves play an essential role in maintaining the quality, safety, and reputation of hotels. Therefore, hotels need to give adequate attention to the management of replacement reserves and allocate sufficient funds for the maintenance and replacement of aging or damaged equipment and facilities.